2021
DOI: 10.1007/s42452-021-04163-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of metal–organic frameworks (MOFs) MIL-100(Fe) functionalized with thioglycolic acid and ethylenediamine for removal of eosin B dye from aqueous solution

Abstract: The interaction of eosin B dye from aqueous solution with MIL-100(Fe) and functionalized MIL-100(Fe) metal–organic frameworks (MOFs) is reported in this study. MIL-100(Fe) was prepared and functionalized with thioglycolic acid (TH) and ethylenediammine (ED) separately by incorporating the thiol (–SH) and the amine (–NH2) group of the functionalizing agents into the open metal sites of the MIL-100(Fe) to obtain the acidic (TH-MIL-100) and basic (ED-MIL-100) forms of the MOF respectively. Characterization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
1
11
0
4
Order By: Relevance
“…This suggests that the coordination of the metal site Bi and the carboxylate group (–COOH) causes all the functional groups in the thiophene ring to shift to lower wavenumbers, which is also due to the change in vibration intensity and frequency [46] , [49] . Near 800 cm −1 , there are two peaks with low intensity, which are generally attributed to the vibration of metal–oxygen bonds (M−O) [23] , [29] , [46] . For the Bi-TDC system, they are the stretching vibrations of Bi-O bonds, and the two small peaks correspond to the two different chemical environments of Bi-O bonds [37] , [49] , which are consistent with the two coordination modes of bridging and terminal coordination mentioned above [15] , [19] , [50] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the coordination of the metal site Bi and the carboxylate group (–COOH) causes all the functional groups in the thiophene ring to shift to lower wavenumbers, which is also due to the change in vibration intensity and frequency [46] , [49] . Near 800 cm −1 , there are two peaks with low intensity, which are generally attributed to the vibration of metal–oxygen bonds (M−O) [23] , [29] , [46] . For the Bi-TDC system, they are the stretching vibrations of Bi-O bonds, and the two small peaks correspond to the two different chemical environments of Bi-O bonds [37] , [49] , which are consistent with the two coordination modes of bridging and terminal coordination mentioned above [15] , [19] , [50] .…”
Section: Resultsmentioning
confidence: 99%
“…Thiophene-2,5-dicarboxylic acid (H 2 TDC) is a heterocyclic organic compound with a thiophene ring and two carboxylic acid groups [23] . It can serve as a bridging ligand for metal–organic frameworks (MOFs), which are porous materials consisting of metal ions and organic linkers [24] .…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Table 3, the developed method of this study was also compared with previously reported methods for EB removal. According to the comparative investigation, all the compared factors for EB removal using synthesized TMU‐24 is quite competitive or even better than the other available adsorbent materials 1,47–53 …”
Section: Resultsmentioning
confidence: 99%
“…Analisis difraksi sinar-X diperlukan MOFs untuk menentukan kristalisasi serta pembentukan komposit dan ikatan heterojunction yang terjadi. [46]. Jadi, dari analisis difraksi sinar-X juga dapat mengindikasikan keberhasilan fungsionalisasi MOFs melalui pergeseran puncak difraksi.…”
Section: 𝐷 = 𝑘 𝜆 𝛽 𝑐𝑜𝑠𝜃unclassified
“…Tella et al (2021) berhasil mensintesis MOFs MIL-100 dengan menggunakan metode refluks dimana hasil pemindaian SEM ditunjukkan Gambar 10(a). MIL-100 memiliki morfologi permukaan kristalin halus sebelum dilakukan modifikasi dan setelah dimodifikasi berubah menjadi kasar (Gambar 10(b)) akibat adanya distorsi pada kerangka MOFs termodifikasi [46]. Kemudian, Chen et al (2019) berhasil mensintesis MOFs berbasis MIL-100 dan MIL-101 dengan metode hidrotermal.…”
Section: Analisis Morfologiunclassified